Empowering Primary School Teachers: Strategies for Enhancing Informatization Teaching Skills - Jing Zhang; Jesse Balinas (International Journal of Education and Humanities, 2026)
This study analyzes the information-based teaching abilities of primary school teachers in mathematics and English subjects, focusing on the factors influencing their ICT teaching capabilities. Using a mixed-methods approach, the study employs a combination of questionnaire surveys and interviews to collect both quantitative and qualitative data. It investigates the demographic profiles of teachers, the current situation and challenges related to ICT teaching, and the factors affecting their ICT proficiency. Additionally, it explores strategies to enhance ICT teaching abilities, evaluates the effectiveness of these strategies, and provides recommendations for improving ICT integration in primary education. The findings reveal that teachers' ICT teaching abilities are influenced by factors such as age, sex, and teaching experience. Younger teachers, particularly those aged 21-31, are more familiar with technology, while older teachers require structured professional development. Common challenges include technical problems, insufficient training, and limited access to resources. The study highlights that teacher training, educational policy support, and resource accessibility are crucial factors influencing ICT teaching effectiveness. Key strategies for enhancing ICT teaching abilities include structured professional development, collaborative learning, and improved resource accessibility. The implementation of these strategies has positively impacted ICT integration, but challenges related to resources and continuous professional development remain. Furthermore, the study reveals that ICT-related challenges are consistent across demographic groups, suggesting the need for institution-wide interventions. Factors such as teacher training mechanisms and policy support did not significantly vary across demographic profiles, indicating that systemic factors are more influential than individual characteristics